Seroprevalence of SARS‐CoV‐2 antibodies in front‐line pediatric health care workers. Issue 3 (16th May 2022) - Wilkins, Hannah; Jastaniah, Ebaa; Spray, Beverly; Forrest, James C.; Boehme, Karl W.; Kirkpatrick, Catherine; Boyanton, Bobby L.; Spiro, David M.; Crawley, Lee; Quang, Lawrence; Kennedy, Joshua L.
ABSTRACT: Objective: The goal of this study was to determine the prevalence of SARS‐CoV‐2 infections in pediatric front‐line health care workers (HCWs) using SARS‐CoV‐2 serum antibodies as an indicator of infection. Methods: In this cross‐sectional study, we collected blood samples and survey responses from HCWs in a 38‐bed pediatric emergency department. Serum antibodies to SARS‐CoV‐2 (IgM and/or IgG) were measured using a 2‐step enzyme‐linked immunosorbent assay (ELISA) to detect antibodies against the Spike protein receptor binding domain (RBD), the ectodomain of Spike (S), and the nucleoprotein (N). Results: We collected survey responses and serum samples from 54 pediatric front‐line HCWs from October 2020 through April 2021. Among the 29 unvaccinated HCWs, 4 (13.7%) had antibodies to SARS‐CoV‐2. For the 25 vaccinated HCWs, 10 (40%) were seropositive; 3 were <10 days from the first vaccine dose and 7 were ≥10 days after the first dose. Two of the 10 seropositive vaccines had a prior positive reverse transcription polymerase chain reaction test. Individuals ≥10 days from receiving the first vaccine dose were 37.5 (95% CI: 3.5–399.3) times more likely to have SARS‐CoV‐2 antibodies than unvaccinated individuals or those <10 days from first vaccine dose. Conclusions: Evidence of widespread SARS‐CoV‐2 infections was not found in unvaccinated front‐line HCWs from a pediatric ED as of April 2021. Future work will be required to determine the reasons underlying the lower SARS‐CoV‐2 antibody prevalence compared to adult HCWs.